Analysis of Serum Prostate-Specific Antigen Levels in Men Aged 40 Years and Older in Yasuj, Iran - Mehrabi, Sadrollah; Ghafarian Shirazi, Hamidreza; Rasti, Mahmoud; Bayat, Babak (Urology Journal, 2009)
Introduction: Serum prostate-specific antigen (PSA) is still the simplest marker for early diagnosis and follow-up of prostate cancer. Because racial differences in PSA levels have been found, we performed this study to determine the reference level of serum PSA for men in Yasuj, in southwest Iran. Materials and Methods: Men aged 40 years and older who had been referred to any of the Yasuj hospitals for a blood cell count for any reason were randomly selected. Those with a history of prostate cancer, prostatitis, urinary tract infection, bladder outlet obstruction, or transurethral procedures were excluded. Blood samples were taken, and PSA levels were measured. Results: Prostate-specific antigen levels in the 95th percentile were 1.35 ng/mL, 1.85 ng/mL, 3.2 ng/mL, and 4.4 ng/mL for men aged 40 to 49, 50 to 59, 60 to 69, and older than 69 years, respectively. Mean serum PSA levels were 0.7 ng/mL, 0.9 ng/mL, 1.6 ng/mL, and 2.2 ng/mL, respectively. Conclusion: A comparison of our results with those from studies in the United States and Japan shows that the reference PSA level in our society is significantly lower than that for white and black Western men, and slightly lower than that for Japanese men. Although we examined men with no history of prostate cancer, cancer was not ruled out by diagnostic test; hence, our results may be overestimated. Further investigations in Iran are warranted.